Case study : Veloce Food Industry Sdn. Bhd. / Abdul Hafiz Irham Abdul Karim - Abdul Karim, Abdul Hafiz Irham (2020)
Veloce Food Industry Sdn. Bhd. was established in March 2016 soon after year of research and development on the wide usage and application of rice grain in the ever demanding food market. Thier first inaugural product entered local market under the trade name NASGERA instant rice , acclaimed them as the pioneer and fore runner of instant rice producer in Malaysia. Since then they constantly improve their product range and variation of rice cuisine and favorite rice dishes. Veloce Food Industry Sdn. Bhd. are fully owned Bumiputra company, registered and complied to the local authority certification and accreditation, They are also registered with Halal Jakim (HALAL), Halal Development Corporation (HDC), Ministry of Agriculture (MOA) , MATRADE , Lembaga Kemajuan Ikan Malaysia (LKIM), MARA , PPIM and many other governing bodies in Malaysia. Their pledge is to continue to produce rice base product with innovative, multicultural, international delicious rice dishes and cuisine under the trade name NASGERA .